2010
DOI: 10.1016/j.jip.2010.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Spiroplasma infection in Drosophila melanogaster: What is the advantage of killing males?

Abstract: Male-killing bacteria are maternally inherited agents that cause death of sons of infected females. Their transmission rate is commonly high but imperfect and also sensitive to different environmental factors. Therefore, the proportion of infected females should be reduced in each generation. In order to explain male-killers spread and persistence in host population, a mechanism resulting in the relative increase of infected females must outweigh the losses caused by the imperfect transmission. The resource re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
1
15
0
1
Order By: Relevance
“…On nutrient rich media, we found that despite increasing early egg production Spiroplasma infection status did not affect the total number of eggs laid over a 14-day period. The Spiroplasma -induced early increase in egg production has been described previously for other Spiroplasma strains (Ebbert, 1991; Martins et al, 2010). While the mechanistic basis of this increase is unknown, it offers a possible explanation for the greater number of eggs laid by Spiroplasma -infected flies on nutrient poor media, where the majority of eggs laid by all flies are in the first 2 days post-eclosion.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…On nutrient rich media, we found that despite increasing early egg production Spiroplasma infection status did not affect the total number of eggs laid over a 14-day period. The Spiroplasma -induced early increase in egg production has been described previously for other Spiroplasma strains (Ebbert, 1991; Martins et al, 2010). While the mechanistic basis of this increase is unknown, it offers a possible explanation for the greater number of eggs laid by Spiroplasma -infected flies on nutrient poor media, where the majority of eggs laid by all flies are in the first 2 days post-eclosion.…”
Section: Discussionsupporting
confidence: 60%
“…Experimental studies are generally in line with this prediction, for example Wolbachia and Spiroplasma have relatively minor effects on host fitness (Martins et al, 2010; Unckless and Jaenike, 2012), however, fitness costs usually become apparent as hosts age (Ebbert, 1991; Min and Benzer, 1997; Fry et al, 2004). For endosymbionts that colonize the germline from the adult soma, it has been demonstrated that endosymbiont titers are positively correlated with transmission fidelity (Dyer et al, 2005; Unckless et al, 2009).…”
Section: Introductionmentioning
confidence: 77%
“…Therefore, it appears that the selective advantage conferred by defense alone does not guarantee Spiroplasma persistence. Nevertheless, it is possible that a combination of defense and other net fitness benefits conferred by this male-killing strain (i.e., higher fecundity of wild-caught flies and faster development; Martins et al, 2010) ensure its persistence. Furthermore, our experiment was limited to a few host backgrounds (seven isofemale lines not known to harbor Spiroplasma naturally), and two highly virulent wasp strains.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether direct or indirect fitness effects of male-killing are sufficient to maintain such infection frequencies, particularly those at the higher end. Martins et al (2010) found that MSRO-infected wild females have a higher fecundity (at least over four consecutive days), and their progeny develop faster. In contrast, Montenegro et al (2006) reported no effect of MSRO on larval competitive ability or adult fecundity of D. melanogaster Canton-S strain.…”
Section: Introductionmentioning
confidence: 90%
“…However, it seems doubtful that these factors play a significant role in the Spiroplasma-Drosophila male-killing endosymbiosis (Hurst and Majerus, 1993;Martins et al, 2010). It also increases the opportunity of horizontal transfer of the symbiont following male death.…”
Section: Effect On Host Fitnessmentioning
confidence: 99%